Exploring the Theories of Radicalization - Maskaliūnaitė, Asta (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
After the London bombings in July 2005, the concern of terrorism scholars and policy makers has turned to “home-grown” terrorism and potential for political violence from within the states. “Radicalization” became a new buzz word. This article follows a number of reviews of the literature on radicalization and offers another angle for looking at this research. First, it discusses the term “radicalization” and suggests the use of the following definition of radicalization as a process by which a person adopts belief systems which justify the use of violence to effect social change and comes to actively support as well as employ violent means for political purposes. Next, it proposes to see the theories of radicalization focusing on the individual and the two dimensions of his/her motivation: whether that motivation is internal or external and whether it is due to personal choice or either internal (due to some psychological traits) or external compulsion. Though not all theories fall neatly within these categories, they make it possible to make comparisons of contributions from a variety of different areas thus reflecting on the interdisciplinary nature of the study of terrorism in general and radicalization as a part of it.